2010
DOI: 10.1039/b904091a
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed azide–alkyne cycloaddition (CuAAC) and beyond: new reactivity of copper(i) acetylides

Abstract: Copper-catalyzed azide-alkyne cycloaddition (CuAAC) is a widely utilized, reliable, and straightforward way for making covalent connections between building blocks containing various functional groups. It has been used in organic synthesis, medicinal chemistry, surface and polymer chemistry, and bioconjugation applications. Despite the apparent simplicity of the reaction, its mechanism involves multiple reversible steps involving coordination complexes of copper(I) acetylides of varying nuclearity. Understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
1,123
0
24

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,920 publications
(1,165 citation statements)
references
References 69 publications
(118 reference statements)
18
1,123
0
24
Order By: Relevance
“…On the other hand, based on the kinetic orders of copperA C H T U N G T R E N N U N G (I/II)/TBTA complexes determined by Finn et al and us, we incline to argue that TBTA-assisted CuAAC reactions may take a different pathway than the ligand-free version of the reaction, which has been shown to be second-order in copper. [25,28,29] The kinetic orders of the reaction that involves 1-ethynylcyclohexanol reveal interesting substrate-dependent kinetic behaviors. Compared to phenylacetylene, 1-ethynylcyclohexanol carries a similar kinetic order of 1.5 ( Figure 9).…”
Section: Mechanistic Investigations Of the Tbta-assisted Cua C H T U mentioning
confidence: 99%
“…On the other hand, based on the kinetic orders of copperA C H T U N G T R E N N U N G (I/II)/TBTA complexes determined by Finn et al and us, we incline to argue that TBTA-assisted CuAAC reactions may take a different pathway than the ligand-free version of the reaction, which has been shown to be second-order in copper. [25,28,29] The kinetic orders of the reaction that involves 1-ethynylcyclohexanol reveal interesting substrate-dependent kinetic behaviors. Compared to phenylacetylene, 1-ethynylcyclohexanol carries a similar kinetic order of 1.5 ( Figure 9).…”
Section: Mechanistic Investigations Of the Tbta-assisted Cua C H T U mentioning
confidence: 99%
“…4 The report from Scripps, meanwhile, provides a procedure for the reaction in solution, employing convenient in situ reduction of copper(II) sulfate with ascorbic acid to form the necessary Cu(I) species. 5 This Cu-catalyzed azide alkyne cycloaddition (CuAAC) has since been applied to a great extent, [9][10][11][34][35] not only in chemistry but also in related areas such as biology [36][37][38] and new materials, 39 mainly due to the experimental simplicity of the reaction, as well as its robustness and the high yields obtained. The reaction is tolerant to almost every functional group, can be performed in a wide range of solvents, including water, and has a very favorable atom economy 40 as all ingoing components are, at least in theory, incorporated into the product.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5] This copper-catalyzed azide alkyne cycloaddition (CuAAC) has since found widespread use even outside the chemistry community. [6][7][8][9][10][11] However, a method to form the corresponding 1,5-disubstituted 1,2,3-triazole isomer was also needed. In 2005 this problem was solved by Fokin and Jia,12 who showed that by exchanging copper for ruthenium, this class of isomers could also be accessed.…”
Section: Peptide Side-chain Mimeticsmentioning
confidence: 99%
“…The triazoleforming copper-catalysed alkyne-azide cycloaddition (CuAAC) reaction is an attractive chemical reaction that allows such synthetic control, due to its wide applicability. 20 The tribromo-complex, [Eu.L 1 ] can be easily transformed into the corresponding triazide, owing to the enhanced electrophilicity of the C-Br bond. Interestingly, only two examples of lanthanide complexes incorporating pyridyl-triazole-aryl acyclic chelating ligands appear in the literature (Fig.…”
Section: Introductionmentioning
confidence: 99%